New species of Polycystididae (Platyhelminthes: Kalyptorhynchia) from Cuba and the Pacific coast of Panama - Diez, Yander L.; Sanjuan, Claudia; Monnens, Marlies; Artois, Tom (European Journal of Taxonomy, 2023)
Four new species of marine polycystidid microturbellarians (Platyhelminthes, Kalyptorhynchia) are described from Cuba and Panama. These species are Brachyrhynchoides ortizi sp. nov., Djeziraia adriani sp. nov., Phonorhynchoides lalanai sp. nov., and Sabulirhynchus ibarrae sp. nov. All species occur in Cuba, and P. lalanai sp. nov. was also retrieved from the Pacific coast of Panama. From the latter locality, we also report Sabulirhynchus axi Artois & Schockaert, 2000. All species are readily distinguished from their congeners by the morphology of the sclerotised structures of the male genital system. The prostatic stylet of B. ortizi sp. nov. is the shortest and widest known for Brachyrhynchoides. Djeziraia adriani sp. nov. can be recognized by its paired seminal vesicles and S-shaped prostate stylet. The prostatic stylet of P. lalanai sp. nov. is proximally twisted and the length proportion between its accessory and prostatic stylet is the largest among all known species of Phonorhynchoides. Sabulirhynchus axi and Sabulirhynchus ibarrae sp. nov. are morphologically similar, yet the latter species is unique due to the characteristic ridge in the middle of the proximally tubular prostatic stylet. With the data available today, a possible explanation of rhabdocoel biogeographic patterns across the Isthmus of Panama remains largely speculative.